At sources of the russian constitutionalism. «Undercover» constitutional projects of the state transformations in Russia in the 18th - the beginning of the 19th centuries - N. A. Omelchenko (Управление)
Article is devoted to a problem of development of the constitutional ideas in pre-revolutionary imperial Russia having, according to the author, importance for judgment of features of political development of Russia and the Russian constitutionalism, in particular. The thought that the first projects of the constitutional restriction of the monarchy in Russia have appeared long before development of the known plan of the state transformation of M. M. Speransky and the constitutional projects of Decembrists is proved in article. The author investigates value of the first in political history of Russia of the projects of restriction the monarchy representative institutions which have arisen during «palace revolutions» («events of year 1730», the constitution project of Panin-Fonvizin, the project «The appointed diploma to the Russian people» by the count A. R. Vorontsov, and others). In article the attention is paid that the majority of these projects were created by unofficially narrow group of supporters in the mode of strict privacy is paid and were result of fight in ruling elite for political influence. At the end of 18th - the beginning of the 19th century supporters of the constitutional board were the representatives of the most progressive noble aristocracy suggesting to carry out transition to constitutional monarchy by means of the constitutional reforms, there are more and more popular ideas of cancellation of the serfdom, development of local government and others. The special place in article is allocated to the characteristic of the constitutional project of year 1820 of «The state authorized diploma of the Russian Empire» («The authorized diploma of Novosiltsev») prepared by N. N. Novosiltsev at the request of tsar Alexander I, representing, according to the author of article, the considerable phenomenon in development of the Russian constitutionalism confirming enough high standard of knowledge and the cultures of that time in the field of state law and the state construction.